Northern spy : a novel - Berry, Flynn, 1986- (Viking, 2021)
"A producer at the Belfast bureau of the BBC, Tessa is at work one day when the news of another raid comes on the air. The IRA may have gone underground after the Good Friday agreement, but they never really went away, and lately, bomb threats, arms drops, and helicopters floating ominously over the city have become features of everyday life. As the anchor requests the public's help in locating those responsible for this latest raid - a robbery at a gas station - Tessa's sister appears on the screen. Tessa watches in shock as Marian pulls a black mask over her face. The police believe Marian has joined the IRA, but Tessa knows this is impossible. They were raised to oppose Republicanism, and the violence enacted in its name. They've attended peace vigils together. And besides, Marian is vacationing by the sea. Tessa just spoke to her yesterday. When the truth of what has happened to Marian reveals itself, Tessa will be forced to choose: between her ideals and her family, between bystanderism and action. Walking an increasingly perilous road, she fears nothing more than endangering the one person she loves more fiercely than her sister: her infant son. A riveting and exquisite novel about family, terror, motherhood, betrayal, and the staggering human costs of an intractable conflict, Northern Spy cements Flynn Berry's status as one of the most sophisticated and accomplished authors of crime and suspense novels working today"--